RESPON PERTUMBUHAN DAN HASIL TANAMAN KANGKUNG DARAT (Ipomea reptans poir) TERHADAP PEMBERIAN PUPUK KANDANG DAN BIOURINE SAPI - Modesta Yuliana Hartika; I Made Sukerta; Listihani; Bagus Putu Udiyana (Faculty of Agriculture and Business, Universitas Mahasaraswati Denpasar , Kec. Denpasar Utara, Kota Denpasar, Bali 80233, 2023)
Kale plans is one type of horticultural plant that is easy to cultivz kale plants can grow optimally if they are planted on land that has high enough macro and micro nutrients and loose soil conditions, one of the macro nutrients needed by this vegetable is nitrogen nutrients, because nitrogen is a basic nutrient forming proteins, nucleic acids, and chlorophyll that are useful in the process of photosynthesis. This study aims to determine the